Elaboração e caracterização de licores de frutas vermelhas - Pinto, Kelly Moreira (2019)
Fruit consumption has been growing every decade since it is a healthy food due to its functional and nutritional properties, especially bioactive compounds, in which it consists of substances that promote health. Among the fruit species, red fruits, or berries, have been gaining prominence, since they are universally recognized for their rich nutrient composition, especially bioactive compounds, in addition to being appreciated for their sensorial characteristics. Among the fruits present in this group are blackberry (Morus nigra L.), raspberry (Rubus idaeus L.) and strawberry (Fragaria vesca). However, these fruits have high perishability, having a short shelf life. Therefore, for the aggregation of value to fruits, an increase in the useful life for the preservation requires the processing of the same, taking as an example the production of liquor, in which the ingredients are fruit, alcohol, sugar and water, passing a process of alc oholic maceration, filtration, addition of the syrup, bottling followed by aging. Thus, this work was carried out with the objective of evaluating red fruit liqueurs in two different concentrations of sugar, with emphasis on bioactive compounds, besides their sensorial characteristics. For this, tests were initially carried out taking into account some essential factors for the production of liquors, such as fruit quantity, alcohol content and maceration days. After that, pH, soluble solids, titratable acidity, coloration, alcohol content, total sugars, vitamin C, total phenolics, total anthocyanins and antioxidant activity were evaluated through DPPH, ABTS and FRAP methods. For the sensorial analysis, the tests of acceptance and intention of purchase of the produced liquors were carried out. Through the results, the studied fruit liqueurs are considered as sources of bioactive compounds, since these presented a high content of phenolic compounds and consequently a high antioxidant capacity, being that the liquor of blackberry presented higher averages of bioactive compounds, in addition, all the liquors produced were sensorially accepted, with red fruit and raspberry liqueurs highlighted, both in the sweetest treatment.